Development of novel as-cast Ti-Mo-Zr alloys for biomedical applications - Rodrigues, Israel Ramos [UNESP]; De Lima Lopes, Renan Eduardo [UNESP]; Grandini, Carlos Roberto [UNESP] (FapUNIFESP (SciELO), 2021)
Titanium is one of the most utilized metals for orthopedic implants. This element has excellent mechanical and biological properties. As a strategy to develop a new system of alloys that do not cause health problems to the patient, such as the Ti-6Al-4V alloy, a new group of alloys has been designed to meet these expectations. Molybdenum, when associated with titanium, reduces the transition temperature from a to the β phase. Zirconium increases the corrosion resistance, decreases the melting point, and improves the alloy's biocompatibility. The alloys with the beta phase's predominance are the most desirable for biomedical applications due to their higher mechanical compatibility with the bone tissue. This paper presents the preparation of as-cast Ti-10Mo-xZr (x= 30, 40, and 50 wt%) alloys and their characterization by measurements of density, energy dispersive spectrometry (EDS), x-ray diffraction, optical and scanning electron microscope (SEM). The density values were higher than that of pure titanium due to the zirconium and molybdenum. The EDS measurements reveal a suitable stoichiometry of the elements and no impurities contamination. In the x-ray diffraction and microscopy measurements, it was observed only peaks of the beta phase. This new system of Ti-alloys is promising for biomedical applications.
Keywords: Microstructure; Ti-Alloys; Β-phase alloys